In silico Pharmacokinetic and Toxicity Prediction of Compounds from Andrographis paniculata (Burm.f.) Nees. - Izatunnafis, Izatunnafis; Murti, Yosi Bayu; Ari Sudarmanto, Bambang Sulistyo (Journal of Food and Pharmaceutical Sciences, 2023)
Many compounds have been isolated from Andrographis paniculata (Burm. f.) Nees (AP). In drug discovery and development, plant secondary metabolites are popular as resources for drug candidates. A high-quality drug candidate should not only be effective against the therapeutic target, but it should also be safe and have good pharmacokinetic features. This study aimed to predict the pharmacokinetic features and toxicity potencies of 46 compounds from AP using the pKCSM online tool. According to pKCSM prediction, among the forty-six compounds from AP, compound 1 (14-Deoxy-11,12-didehydroandrographolide), compound 2 (14-Deoxyandrographolide), and compound 39 ((-)-beta-Sitosterol) have good pharmacokinetic features and do not have potencies to be mutagenic and hepatotoxic agents. The lethal dosage values (LD50) of compounds 1, 2, and 39, are 1935, 2053, and 2424 (mol/kg), respectively. However, further research is still needed to confirm these predictions.